Identifikasi dan penyimpanan koleksi Museum Zoologi Sekolah Ilmu dan Teknologi Hayati (SITH) Institut Teknologi Bandung Jatinangor - Jainal Ihsan Kaenuwihanulah; Ninis Agustini Damayani; Rully Khairul Anwar (Faculty of Communication, Padjadjaran University, 2021)
The museum has a role as educational and research facilities for visitors. The Museum of Zoologi SITH ITB is one of the museum that has a collection of both wet and dry specimens. Preserved specimens become museum collections that are vulnarable to fragility or damage. Museum helped us to preserve the animals and change it to specimens so that museum visitors could see it. Thus, this study aims to see how to identify and serve collection at the Museum of Zoologi SITH ITB. The research method used was qualitative with case study approach, and the research subjects were museum head, curators, and museum visitors. The data were collected through interviews, observation, and literature review. According to the research results, museum collections are determined based on the policy of selecting animal species to be used as specimens, preservation and conservation methods (display), as well as taxonomic information. The types of animals chosen are those that have a backbone and no backbone, including invertebrates, fish, amphibians, reptiles, birds and mammals through wet and dry preservation. The conservation of the Museum of Zoology SITH ITB collection is carried out through a process of collection analysis, preservation, labeling, and storage. First, in performing the collection analysis process, curators observe animals to be killed for specimens and writes a permission letter to the authorized institution. Second, in performing preservation, curators preserve wet and dry specimen collections according to their own specimens. Third, in labeling activities, curators label wet and dry specimen collections according to the container placement. Finally, in storage activities curators store different collections of wet and dry specimens. Research on the identification and storage of collections at the Museum Zoologi SITH ITB can assist curators in introducing preserved specimens to visitors. The conclusion of the research is that the curators of the Museum Zoologi SITH ITB play an important role in maintaining the collection and introducing the museum collection to visitors, and this makes the collection of the museum to be long-lasting, researchable, and obserevable for all visitors.